Implementasi Asuransi Mikro Syariah Pada Majelis Taklim Melalui Program Majelis Taklim Bertaawun Amanah Takaful - Ade Abdurachman (Diversity: Jurnal Ilmiah Pascasarjana, 2025)
Majelis Taklim, as a popular Islamic study group in Indonesia, has great potential as a channel to spread the benefits of sharia microinsurance. The implementation of sharia microinsurance in Majelis Taklim can provide financial protection for its members, most of whom come from vulnerable economic backgrounds. However, its implementation is not free from various challenges, such as lack of understanding of sharia insurance, trust in financial institutions, and complexity of management. This study aims to examine the opportunities and challenges of implementing sharia microinsurance in Majelis Taklim in Indonesia, as well as to provide strategic recommendations for the success of its implementation. The research methods used are literature studies, interviews with Majelis Taklim administrators and institutions that market sharia insurance programs, namely Amanah Takaful, and secondary data analysis. The results of the study indicate that the implementation of sharia microinsurance in Majelis Taklim through the MT Bertaawun program has great potential to improve the economic welfare of the community, but requires a comprehensive and collaborative approach between various parties